Families with fetal alcohol spectrum disorders: Exploring adoptive parents' experiences of family well-being. (October 2021) - Balcaen, Lisa; Santos, Rob; Roger, Kerstin; Mignone, Javier
Fetal alcohol spectrum disorder (FASD) is the leading non-genetic cause of developmental disability in Canada. It poses many challenges at the individual, family and societal levels. This study explores adoptive parents' experiences of having a child with FASD in their family and how these experiences impact family well-being and, specifically, parenting, family dynamics, sources of support and coping strategies. Using an Interpretive Phenomenological Analysis (IPA) approach, in-depth semi-structured interviews were conducted with eight adoptive parents of children with FASD. Four main themes emerged, each with several subthemes: (1) managing individuals with FASD; (2) navigating family cohesion; (3) psychological warfare; and (4) experiences of supports. Findings showed how FASD affects all aspects of family life and has a constant and cumulative effect on the family's well-being. Hope, community and parents feeling successful in their efforts were found to have strong connections to well-being.